THE LIVER VERSUS BONE CONUNDRUM IN ISOLATED RAISED ALKALINE PHOSPHATASE LEVEL - Renganadan, Krinath; Sarvanandan, Tharsini; Ooi, Ying Guat; Khoo, Jun Kit; Lim, Quan Hziung; Hee, Nicholas Ken Yoong; Vethakkan, Shireene; Lim, Lee-Ling; Paramasivam, Sharmila; Ratnasingam, Jeyakantha; et al. (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Alkaline Phosphatase (ALP) is an enzyme that catalyses the hydrolysis of organic phosphate esters. It is concentrated in the liver, bone, kidney, intestinal mucosa and placenta. When ALP is elevated in isolation, isoenzyme studies using electrophoresis can confirm the source. Here, we describe a case of a patient with an incidental finding of elevated ALP. CASE A 30-year-old female with no known medical illness was referred to the endocrine clinic for an incidental finding of persistently elevated ALP detected during routine blood investigation. She did not report any fractures or myopathy. There were no symptoms or risk factors for liver or connective tissue disease. Clinical examination was unremarkable, with no blue sclera, bony deformities or stigmata of chronic liver disease. Her growth was normal, achieving her mid-parental height of 150 cm. Her laboratory results showed isolated elevation of ALP 226 U/L (N: 45-129) with normal gamma-glutamyl transferase 11 U/L (N: <38), alanine transaminase 11 U/L (N: 10-49), aspartate transaminase 22 U/L (N: <34), phosphate 1.24 mmol/L (N: 0.78-1.65), calcium 2.4 mmol/L (N: 2.2- 2.6), haemoglobin 136 g/L (N: 120-150), white blood cell 9.4 109 /L (N: 4-10) and platelet 230 109 /L (N: 150-400). Liver ultrasonography did not reveal any abnormalities. Further investigation showed a mildly raised parathyroid hormone of 9.4 pmol/L (N: 1.96-8.49) with a low 25-OH Vitamin D level at 31 nmol/L (N: >50). She was started on cholecalciferol. Parathyroid hormone and Vitamin D became normal after treatment with cholecalciferol. Her bone scan and bone density were normal. We excluded Macro-ALP by performing a polyethylene glycol precipitation test. Subsequently, ALP Isoenzyme electrophoresis was done, confirming predominant ALP from the liver at 73% (N: 18-85%), 14% from bone (N: 14-68%), 13% from the intestine (N: <18%). As the patient was asymptomatic and had normal liver function, the hepatologist decided to monitor her biochemically and clinically. CONCLUSION Patients with elevated ALP should be thoroughly investigated and examined to rule out the common treatable causes. In cases of isolated raised ALP, isoenzyme electrophoresis could identify the source with the highest accuracy.